LncRNAs and regulated cell death in tumor cells - Wu, Yingying; Wen, Xiaoling; Xia, Yufang; Yu, Xiao; Lou, Yanhui (Frontiers in Oncology, 2023)
Regulated Cell Death (RCD) is a mode of cell death that occurs through drug or genetic intervention. The regulation of RCDs is one of the significant reasons for the long survival time of tumor cells and poor prognosis of patients. Long non-coding RNAs (lncRNAs) which are involved in the regulation of tumor biological processes, including RCDs occurring on tumor cells, are closely related to tumor progression. In this review, we describe the mechanisms of eight different RCDs which contain apoptosis, necroptosis, pyroptosis, NETosis, entosis, ferroptosis, autosis and cuproptosis. Meanwhile, their respective role in the tumor are aggregated. In addition, we outline the literature that is related to the regulatory relationship between lncRNAs and RCDs in tumor cells, which is expected to provide new ideas for tumor diagnosis and treatment.